Evaluasi Kemampuan Komunikasi Matematis Siswa SMP Pada Materi Sistem Persamaan Linear Dua Variabel - Andriana Siwi Purwandari; Meilani Dwi Astuti; Anik Yuliani (Universitas Sarjanawiyata Tamansiswa, 2018)
The ability of mathematical communication is contained in the curriculum and objectives of mathematics learning. Through mathematical communication is expected to improve students abilities of mathematical concepts. The purpose of this study is to determine the level of mathematical communication ability of junior high school students on the material system of two linear equations. This research is a descriptive research with qualitative approach. The study time was held in the even semester of the academic year 2017/2018. The subjects of the study were students of SMP class VIII in Cimahi city as many as 33 students. Data collection methods used are test methods, observation and documentation. Based on the results of data analysis showed the students mathematical communication ability of SMP on linear equation system two variables were obtained: (1) students ability in reflecting real objects, drawings and diagrams into mathematics idea with percentage of 81,08%; (2) students ability to explain ideas, situations and mathematical relations both orally and in writing using real objects, images, graphs and algebraic expressions with percentage of 33,33%; (3) the ability of students to declare daily events in language or mathematical symbols or to construct an event mathematical model of 18.18%; (4) students ability in explaining and making math questions studied for 7.58% and (5) students ability in making conjectures, formulating arguments, formulating definitions and generalizations of 7.58%.